2013
DOI: 10.3174/ajnr.a3510
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of Rapid Pediatric Brain MR Imaging at an Academic Institution Including Practice Trends and Factors Affecting Scan Times

Abstract: BACKGROUND AND PURPOSE:In an effort to reduce radiation exposure in children requiring regular follow up for shunted hydrocephalus, our institution implemented a rapid brain MR imaging protocol. The purpose of this study was to review an academic practice experience with pediatric rapid brain MR imaging without patient sedation in the evaluation of hydrocephalus and a limited group of other conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…In our study, the sensitivity and specificity of QB-MRI were not significantly different from that of CT for shunt evaluation. In earlier studies, Iskandar et al, 7 Ashley et al, 2 O'Neill et al, 13 Rozovsky et al, 15 and Niderhauser et al 12 reported on image quality, catheter visualization, and image acquisition time for QB-MRI for shunt-dependent hydrocephalus (also referred to as rapid-sequence MRI [RS-MRI] or rapid brain MRI). The acquisition time and procedure time for QB-MRI reported by prior studies are similar to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the sensitivity and specificity of QB-MRI were not significantly different from that of CT for shunt evaluation. In earlier studies, Iskandar et al, 7 Ashley et al, 2 O'Neill et al, 13 Rozovsky et al, 15 and Niderhauser et al 12 reported on image quality, catheter visualization, and image acquisition time for QB-MRI for shunt-dependent hydrocephalus (also referred to as rapid-sequence MRI [RS-MRI] or rapid brain MRI). The acquisition time and procedure time for QB-MRI reported by prior studies are similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Niederhauser et al reviewed rapid brain MRI examinations in non-sedated children and found adequate diagnostic visualization of ventricular size in nearly 400 examinations. 12 At Site 1, the estimated imaging time for noncontrast brain CT is 5 minutes with an actual examination time of 5-10 seconds versus the estimated imaging time of 3-5 minutes for QB-MRI with an examination time of 45 seconds per plane, using axial, sagittal, and coronal imaging planes. The vast majority of patients did not require moderate or deep sedation for either modality.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies compared ultra-fast MRI techniques to conventional MRI techniques [13][14][15][16][17][18]; eight reviewed the clinical use of ultra-fast techniques [6][7][8][19][20][21][22][23]; one compared two ultrafast techniques [24]; one compared ultra-fast and standard MRI to CT [25]; and one compared ultra-fast MRI to CT [26]. Six studies compared techniques using oversampling of k-space to conventional MRI [9,[27][28][29][30][31]; and one compared an ultra-fast technique to a technique using oversampling of kspace [32].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…11 Since then, UF-MR imaging has been validated with similar test characteristics for the evaluation of possible shunt failure (assessment of ventricular size and catheter visualization) compared with head CT. [17][18][19] Diagnostic image quality and the short image-acquisition time of UF-MR imaging have also been reported. [11][12][13][14][15] Despite the aforementioned publications, consistent nationwide use of this radiation-free neuroimaging technique has been somewhat limited. The palpable growing demand to improve quality and safety in imaging is now requiring radiologists to take leadership responsibilities, beyond simply reading a timely accurate radiology examination.…”
Section: Figmentioning
confidence: 99%
“…Ultrafast brain MR imaging (UF-MR imaging) offers reliable visualization of the ventricular catheter and superior anatomic detail of the ventricular system; therefore, diagnostic accuracy of the test is not reduced as the child benefits from radiation-free imaging. [11][12][13][14][15] However, in our experience, these MR imaging protocols are limited to relatively few centers or are performed only during certain hours of the day.…”
mentioning
confidence: 99%